Photooxidative Keto-Trifluoromethylation of Styrenes by Means of an Anthraquinone-Based Organocatalyst - Yamaguchi, Eiji; Kamito, Yuji; Matsuo, Kazuki; Ishihara, Jun; Itoh, Akichika (Synthesis, 2018)
α-Trifluoromethyl ketones are versatile building blocks for the synthesis of various trifluoromethyl-functionalized molecules. Although there are significant advantages in the development of methods toward direct transformations of styrenes into α-trifluoromethyl ketones, most procedures leading to α-trifluoromethyl ketones require heavy- or transition-metal-based complexes. Herein, a novel method is developed for the synthesis of α-trifluoromethyl ketones via anthraquinone-catalyzed photooxidative keto-trifluoromethylation of styrenes with the readily available Langlois reagent (CF3SO2Na) under an oxygen atmosphere. The reactions proceed smoothly to give the products in moderate to excellent yield with good selectivity.
Keywords: anthraquinone; trifluoromethylation; trifluoromethyl radical; radical reaction; photoreaction